Surgery patients’ perception about anesthesia and role of anesthesiologist - Piya, Roshan; Shrestha, Anil; Pradhan, Manisha; Amatya, Shirish Prasad; Shrestha, Aimi; Poudel, Sangeeta (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Anesthesiologists play an important role in the management of peri-operative risk and the perception of patients towards anesthesia and the role of anesthesiologists are often underestimated. Newer initiatives are required to increase communication with patients and educate them about the importance of anesthesia during surgery. The study aims to assess perception in relation to education level and patients’ previous exposure to anesthesia about anesthesia and the role of the anesthesiologist. Method: A cross-sectional, predesigned Nepali questionnaire-based study was conducted after approval from the Institutional Review Committee (IRC), Patan Academy of Health Sciences. A total of386 above 14 years old hospital admitted patients undergoing elective surgery in different departments of Patan Hospital were included. Data was collected during the pre-anesthetic evaluation one day before surgery. Perception of patients in relation to educational level and previous exposure to surgery and chi-square test was done at p<0.05 statistically significant. Result: Among 386 participants, 246(63.4%)participants had no previous anesthetic exposure and showed significant difference on perception about the meaning of anaesthesia and administration of anesthetic medicine among patients with previous exposure of anaesthesia and without. Among participants,38(9.8%) were uneducated and awareness about anesthesia and different techniques of anesthesia was poor. Only 193 (50%) participants knew that anesthetic medicine is given by anesthesiologist and 131 (33.9%) knew that anaesthesiologist were responsible for controlling vital signs during surgery. Study revealed poor knowledge regarding the role of anesthesiologist and showed a statistically significant difference in educational level of patient. Conclusion: Perception on anesthesia and role of anaesthesiologist was less in relation to educational level and previous exposure to anesthetic among study participants.